Character Education Through Primary Social Science Learning - Ramayani, Sri (Berpusi Publishing, 2024)
Character education is a necessity in the current learning era. Because character education teaches students to have character values that need to be developed, especially in social studies lessons. This research utilizes library studies through library references, the researcher provides a complex picture, analyzes the report's words in detail from the respondent 's perspective and carries out research studies. This research data collection was collected from the results of several researchers, through various reference materials originating from journal articles, documentation, and through various teaching materials that examine Character Education in elementary school social studies lessons. This research utilizes a contextual approach. The aim of this research is to see how character education is applied to elementary school social studies lessons. This research method includes literature study. The results of the research, namely instilling character values, can be applied or developed in social science (IPS) lessons. Implementation can go through various stages during social studies lessons.